MODERNIZATION OF THE STAND FOR DETERMINING THE FORCE CHARACTERISTICS OF THE SUSPENSION BUSHES SUSPENSION VEHICLES - D. A. Tihov-Tinnikov; V. S. Baradiev; A. V. Bykov; V. G. Vlasov (Вестник СибАДИ)
The article discusses the modernization of stand to obtain a stable control action on the test cushion, the car’s suspension. The paper describes the procedure of testing bushings on the stand presented events for improvement of experimental equipment. The characteristics of the control action on the bushing, obtained with the upgraded stand, modes of 0.17 and 1.33 Hz. The performed work and the obtained results allow to conclude about the suitability of the upgraded stand for research of silent blocks in order to develop highly effective and informative method of diagnosis.